Geographic variation of Moenkhausia bonita (Characiformes: Characidae) in the rio de la Plata basin, with distributional comments on M-intermedia - Vanegas-Rios, James Anyelo; Britzke, Ricardo [UNESP]; Mirande, Juan Marcos (Soc Brasileira Ictiologia, 2019)
Moenkhausia bonita occurs in numerous additional localities from the Bermejo, Parana, Paraguay, and Uruguay river basins. Given that this finding greatly expands the distributional range of M. bonita, we carried out an intraspecific comparison, using multivariate methods for 18 morphometric and eight meristic characters taken from a comprehensive sample of 536 specimens. All localities were distributed in four major geographic groups as follows: Bermejo, Parana, Paraguay, and Uruguay. Results of the morphometric comparisons showed significant differences among the studied groups except between the Paraguay and Uruguay groups. Statistical differences in meristic values were found for most between-group comparisons, especially in those resulting from discriminant canonical analyses (DCA). Specimens from the Bermejo basin were the most distinct group in most morphological comparisons. However, the overall subtle differences found in body morphology likely reflect intraspecific variation within M bonita and seem to be mainly influenced by spatial and environmental features of drainages. As M. bonita was previously identified as M. intermedia in the rio de La Plata basin, distributional confluents on the latter species in that basin are provided.
Keywords: Allometry; Argentina; Moenkhausia; Morphological variation; Widespread species